Ethical challenges experienced by UK military medical personnel deployed to Sierra Leone (operation GRITROCK) during the 2014–2015 Ebola outbreak: a qualitative study - Draper, Heather; Jenkins, Simon (BMC medical ethics, 2017)
Background As part of its response to the 2014 Ebola outbreak in west Africa, the United Kingdom (UK) government established an Ebola treatment unit in Sierra Leone, staffed by military personnel. Little is known about the ethical challenges experienced by military medical staff on humanitarian deployment. We designed a qualitative study to explore this further with those who worked in the treatment unit. Method Semi-structured, face-to-face and telephone interviews were conducted with 20 UK military personnel deployed between October 2014 and April 2015 in one of three roles in the Ebola treatment unit: clinician; nursing and nursing assistant; and other medical support work, including infection control and laboratory and mortuary services. Results Many participants reported feeling ethically motivated to volunteer for deployment, but for some personal interests were also a consideration. A small minority had negative feelings towards the deployment, others felt that this deployment like any other was part of military service. Almost all had initial concerns about personal safety but were reassured by their pre-deployment 'drills and skills', and personal protective equipment. Risk perceptions were related to perceptions about military service. Efforts to minimise infection risk were perceived to have made good patient care more difficult. Significantly, some thought the humanitarian nature of the mission justified tolerating greater risks to staff. Trust in the military institution and colleagues was expressed; many participants referred to the ethical obligation within the chain of command to protect those under their command. Participants expected resources to be overwhelmed and ‘empty beds’ presented a significant and pervasive ethical challenge. Most thought more patients could and should have been treated. Points of reference for participants’ ethical values were: previous deployment experience; previous UK/National Health Service experience; professional ethics; and, distinctly military values (that might not be shared with non-military workers). Conclusion We report the first systematic exploration of the ethical challenges face by a Western medical military in the international response to the first major Ebola outbreak. We offer unique insights into the military healthcare workers’ experiences of humanitarian deployment. Many participants expressed motivations that gave them common purpose with civilian volunteers.